(untitled) (Research, Society and Development, 2023)
The high prevalence of microorganisms resistant to antimicrobials commonly used in clinical practice has impacted healthcare services due to a reduction in treatment options for patients. Thus, research involving the antimicrobial activity of essential oils (EO) was carried out as possible therapeutic alternatives. The objective of this work was to review the literature and experimentally determine the antimicrobial activity of Mentha piperita and Citrus limon EO against the pathogens Staphylococcus aureus, Escherichia coli, Pseudomonas aeruginosa and Candida albicans. The bibliographic search and selection of scientific articles were carried out in the Pubmed, Virtual Health Library and Scielo databases, adapting the indexers for each database. Complete, open access articles published between 2016 and 2022 were selected. Antimicrobial activity was evaluated from reference microorganisms using the agar disk diffusion method according to methodologies recommended by CLSI and BrCAST. The bibliographic research searched for 533 articles, of which 25 were selected for analysis. The evaluation of the EO from M. piperita showed activity against E. coli, S. aureus and C. albicans and the EO from C.limon showed activity against C. albicans. None of the EO tested showed activity against P. aeruginosa. The data from this work highlight the potential of these EOs against pathogens important to human health and suggest the need for new studies against other emerging pathogens for public health, in addition to better understanding their applicability as a natural and safe alternative for controlling infections. bacterial and fungal.